Flouting Grice’s Maxims in a Jordanian TV Talk Show - Al-Mazari, Wasfi Y.; Rababah, Luqman M. (Jordan Journal of Modern Languages & Literatures, 2024)
This study investigates flouting Grice’s maxims in Sawt Al-Mamlakah, a Jordanian TV talk show. It aims at identifying the types, functions, and frequency of these flouted maxims. Using descriptive qualitative research, the data were analysed within Grice’s (1975) conversational maxims. The study findings reveal that all four maxims were flouted, with quantity being the most flouted, followed by relation, manner, and quality, respectively. Strategies for flouting included evading questions, providing lengthy or irrelevant responses, and sometimes creating a fun atmosphere. Communication breakdowns were not common though they were observed in a few instances. Flouting appeared context-dependent, serving various purposes like collaboration, elaboration, maintaining social relationships, politeness, image protection, expressing agreement or disagreement, satisfaction or dissatisfaction, refraining from sharing sensitive information, and emphasizing points. The study recommends further research on the same show over other periods of time and on maxim flouting in other Arab talk shows.